2016
DOI: 10.1016/s2214-109x(16)30133-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disease outcomes after severe acute malnutrition in Malawian children (ChroSAM): a cohort study

Abstract: SummaryBackgroundTackling severe acute malnutrition (SAM) is a global health priority. Heightened risk of non-communicable diseases (NCD) in children exposed to SAM at around 2 years of age is plausible in view of previously described consequences of other early nutritional insults. By applying developmental origins of health and disease (DOHaD) theory to this group, we aimed to explore the long-term effects of SAM.MethodsWe followed up 352 Malawian children (median age 9·3 years) who were still alive followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
213
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(230 citation statements)
references
References 39 publications
14
213
0
3
Order By: Relevance
“…Severe wasting increases the incidence and severity of common childhood illnesses like diarrhoea and pneumonia (Chisti et al, ; Jones & Berkley, ; Talbert et al, ). Severe wasting in children aged less than 6 months of postnatal life may also affect long‐term developmental outcomes (Lelijveld et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Severe wasting increases the incidence and severity of common childhood illnesses like diarrhoea and pneumonia (Chisti et al, ; Jones & Berkley, ; Talbert et al, ). Severe wasting in children aged less than 6 months of postnatal life may also affect long‐term developmental outcomes (Lelijveld et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Postdischarge mortality is also significant, with studies reporting mortality rates of 8.7% within 3 mo of discharge (3), or ≤18% of all treated cases dying within 1 y of discharge (4). Furthermore, even if the children survive, they suffer from long-term adverse effects, showing patterns of thrifty growth and functional deficits such as weak hand grip and impaired cardiovascular capacity (5). Children with SAM also show impaired cognitive function and substantial attention deficits (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment guidelines have also changed since 1987, which means that the results of their study may need to be re‐evaluated. Although data on the mortality and relapse to SAM of children managed in Community‐Based Management of Acute Malnutrition programmes (uncomplicated SAM) have been reported (O'Sullivan, Lelijveld, Rutishauser‐Perera, Kerac, & James, ; Stobaugh et al, ), only a few papers reported nutritional outcomes of children after treatment from cSAM (Fergusson et al, ; Kerac et al, ; Kerac et al, ; Lelijveld et al, ).…”
Section: Discussionmentioning
confidence: 99%